Characterization of a library of vitamin A-functionalized polymethacrylate-based nanoparticles for siRNA delivery - Klemm, Paul; Huschke, Sophie; Rodewald, Marko; Ehteshamzad, Nadia; Behnke, Mira; Wang, Xinyue; Cinar, Gizem; Nischang, Ivo; Hoeppener, Stephanie; Weber, Christine; Press, Adrian T.; Hoppener, Christiane; et al. (Polymer Chemistry, 2021)
A 60-membered library of vitamin A-functionalized P(MMA-stat-DMAEMA)-b-PPEGMA block copolymers was synthesized by RAFT polymerization. The retinoic acid was coupled to hydroxyl groups present in the hydrophilic PPEGMA block. The polymers were investigated for their ability to encapsulate ribonucleic acids through nanoparticle (NP) formulation using the emulsion/solvent evaporation method. The localization of retinyl in surface-near regions of the NPs was indicated by surface enhanced Raman spectroscopy, and the interaction of the NPs with a retinol binding protein was investigated by an analytical ultracentrifuge. The systematic analysis of the NP library in terms of the encapsulation efficiency of the ribonucleic acids, the toxicity of the NPs, and the cellular uptake helped identifying suitable candidates for cellular internalization studies. The cell uptake was investigated by flow cytometry and fluorescence microscopy and reveals structure dependent uptake behavior of the examined particles.
CRIS-Team Scopus Importer:2023-04-20